Planejamento e organização da competição esportiva pedagógica para crianças e adolescentes: um exemplo no basquetebol - Felipe Canan (Universidade Estadual do Oeste do Paraná, 2018)
The sport competition for children and adolescents needs pedagogical adjustments that, above the result, contribute to sportive and human formation. The objective was to report an experience about a pedagogical basketball competition. Methodology: systematization of experiences discussed in the light of Siedentop (1987) and Freire (2011). As a results, the competition adopted organization, statute and adaptations of rules that sought to contribute to the generation of inclusion, competence and autonomy of players, in relation to basketball, according to the model/proposal of the cited authors. Finally, the positive evaluation by the participants and the finding that it is close to the assumptions of important authors of Sports Pedagogy credit the systematized competition as a good experience to be shared in order to contribute to the formation of peers.